2003
DOI: 10.1088/0031-9155/48/7/305
|View full text |Cite
|
Sign up to set email alerts
|

Washout studies of11C in rabbit thigh muscle implanted by secondary beams of HIMAC

Abstract: Heavy ion therapy has two definite advantages: good dose localization and higher biological effect. Range calculation of the heavy ions is an important factor in treatment planning. X-ray CT numbers are used to estimate the heavy ion range by looking up values in a conversion table which relates empirically photon attenuation in tissues to particle stopping power; this is one source of uncertainty in the treatment planning. Use of positron emitting radioactive beams along with a positron emission tomograph or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 28 publications
2
73
1
1
Order By: Relevance
“…This prohibits the application of compartment models, which are well-established in conventional tracer imaging. Previous animal studies on the washout of 10 C and 11 C implanted ions or 11 C resulting from autoactivation of 12 C beams indicated the existence of a fast (biologic half-life [T 1/2 , biof ] ≈(2-10 s), medium (T 1/2 , biom ≈100-200 s), and slow (T 1/2,bios ≈ 3,000-10,000 s) component of biologic decay in rabbit thigh muscle and brain (15,16). In our offline imaging approach, the fast and medium processes have already decayed at the time of imaging.…”
Section: Calculation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This prohibits the application of compartment models, which are well-established in conventional tracer imaging. Previous animal studies on the washout of 10 C and 11 C implanted ions or 11 C resulting from autoactivation of 12 C beams indicated the existence of a fast (biologic half-life [T 1/2 , biof ] ≈(2-10 s), medium (T 1/2 , biom ≈100-200 s), and slow (T 1/2,bios ≈ 3,000-10,000 s) component of biologic decay in rabbit thigh muscle and brain (15,16). In our offline imaging approach, the fast and medium processes have already decayed at the time of imaging.…”
Section: Calculation Modelmentioning
confidence: 99%
“…Positron emitters such as 11 C and 15 O are produced via nuclear interactions along the protonbeam path, and can be imaged during (online) or shortly after (offline) treatment as a spatial marker of radiation-dose deposition. Previous offline and online phantom experiments indicated the sufficient accuracy of positron emission tomography (PET) imaging for the verification of proton range and field lateral position [(1,2) and citations therein].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the biological washout effect in the metabolism of a living tissue is important for the verification of the absolute activity and the activity distribution of the positron-emitting nuclei induced by the proton irradiation. In studies in which the radioactive ion beam ( 11 C, 10 C) to a rabbit was irradiated, the decay curve has three components of a fast decay (decay constant *2-10 s), medium decay (decay constant *100-200 s), and slow decay (decay constant *3,000-10,000 s) [23,24]. The 50-65% of total activity is the fast and medium components.…”
Section: Measurement Of Activity With Pet-ct Apparatusmentioning
confidence: 99%
“…The coefficient of the effect has been estimated to be the 50-65% of total activity [23,24]. However, the radioactive ion beam was irradiated to a living tissue in the study.…”
Section: Specificity Of Activity Generated In Each Body Tissuementioning
confidence: 99%
“…The simulation of using an on-line system showed losses in activity intensity from transportation to the offline system of up to 75%, depending on the type of tissue. Also, it was found that the effect of biological washout was lower than the previously estimated 50%-65%, although the overall effect was not quantified [37,38] . The study led by Parodi K took nine patients with different types of head and neck cancers and used a PET/…”
mentioning
confidence: 62%